Aachennosgrimmans påverkan på hopphästens beteende - Igelström, Amanda; Larsson, My (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2018)
Bridles has been used to control horses all around the world for approximately 6000 years, and its use is based on application of pressure on sensitive parts of the horse’s head. The originally purpose of the noseband is to relieve strain from the bit and transfer it to the face of the horse, but nowadays nosebands are more commonly used to conceal defective suppleness and conflict behaviours in horses during riding. The reasons seem to be ignorance among riders in relation to what damage a tight noseband can cause a horse’s mental and physical health, but also the interest of succeeding during competition.